RESEARCH OF WAYS OF CONNECTING REINFORCED BARS IN THE PRODUCTION OF REINFORCED CONCRETE PRODUCTS - Sherov, Karibek; Yessirkepova, Ayym; Mikhailov, Valentin; Buzauova, Toty; Mazdubay, Assylkhan; Taskarina, Aizhan (Journal of Applied Engineering Science, 2020)
The authors conduct research on the creation of non-waste technology for the use of reinforcing bars in the manufacture of reinforced concrete products (reinforced concrete). This article presents the results of a study of existing methods for connecting reinforcing bars in the manufacture of reinforced concrete. The connection methods were investigated: mechanical, lap welded. Their advantages and disadvantages are revealed. Welding methods have also been investigated: contact, bathroom docking, contact spot, friction welding. The following main disadvantages inherent in existing methods of connecting reinforcing bars were established: the narrowness of technological capabilities, low quality and accuracy of the connection, the high cost of technological equipment. To address these shortcomings, a new method of friction welding for connecting reinforcing bars is proposed.